Seismogram Analysis of the Earthquakes in Sumatra on WRAB Observation Station: S Wave Velocity Structure on Subduction Zone of Sumatra-Java. - Bagus Jaya Sentosa (Institute for Research and Community Services (LPPM) ITB, 2008)
The S wave velocity structure at subduction zone under Sumatra-Java was investigated through seismogram analysis in time domain and three Cartesian's components simultaneously. The main data set was the comparison between the measured seismogram and the synthetic one, not the travel time data. The synthetic seismogram was calculated with the GEMINI method. The seismogram comparison shows that the global earth mantle of PREMAN gives deviating synthetic seismogram and has later arrival times than the measured one. The gradient Ã¢h in the upper mantle is altered to positive from its negative slope as in the PREMAN model, and positive corrections are added to the zero order of polynomial's coefficients in all earth mantle layers. The excellent fitting, as well as travel time or waveform, were obtained on the surface waves of Love and Rayleigh, the S and SS mantle and repetitive depth waves. The additional positive corrections were also confirmed by a well fitting on the repetitive depth waves. This result expresses that part of the earth mantle that due to tectonic processes has positive anomaly on S wave velocity and vertical anisotropy in all of the earth mantle layers.